Analyze of the ball possession during the offensive process in indoor soccer. Contribute to determine the Collective Efficiency - R. Duarte (Desafio Singular, 2008)
The aim of this study has create a joint of parameters to analyze the ball possession in attack, characterizing the first and the last action, the number of passes and the time of ball possession with finalization or non finalization, the total number of shoots, the number of shoots on goal and the goals. Starting by these parameters, we propose the utilization of Offensive Coefficient Production (CPO) and the Finalization Coefficient Efficiency (CEF), to measure the collective efficiency in indoor soccer. So that, we were utilize the first time of the final world championship at China-Taipei, disputed between Spain and Italy, by the sample. In according with the refers coefficients, Italy is the more efficient team in the match, given that it makes a more elevated percentage of situations with finalization and has more percentage of shoots on goal, that the opposite. The final score is conditioned by the efficacy of team finalization, but we think to be pertinent utilization coefficients, with view to comprehension the team processes in the match. The future goes by the coach access to this information during the game.